Datapedia of the United States, 1790-2000 : America year by year - Kurian, George Thomas (Lanham, MD : Bernan Press, 1994)
Datapedia of the United States presents the most significant historical statistics of the United States in 23 selected areas from 1776 to 1990. In some areas, such as demography, where projections are possible, the data are extended to 2010--P. ix.
Consists chiefly of tables
Includes bibliographical references and index
Keywords: United States -- Statistics